Inhibition of gonadotropin hormone-releasing hormone release by prolactin from GT1 neuronal cell lines through prolactin receptors. - Milenković, L (1994)
High levels of prolactin (PRL) are associated with inhibition of luteinizing hormone secretion in several mammalian species. We asked whether this phenomenon could be explained by a direct inhibitory action of PRL on hypothalamic gonadotropin hormone-releasing hormone (GnRH) neurons. The ability of PRL to suppress GnRH release and expression was tested in the highly differentiated GT1 GnRH cell lines. In static culture, nanomolar concentrations of either rat or mouse PRL inhibited the release of GnRH in a dose-dependent fashion. PRL treatment for 24 hr also decreased GnRH mRNA levels determined by Northern analysis. The cells were shown to express the PRL receptor gene, and the mRNAs for both the short and long forms were present by Northern and PCR analysis, although the short form was more abundant. In Western blots with monoclonal antibody against the rat liver PRL receptor, the short 42-kDa form of the receptor was observed. These results demonstrate that PRL inhibits GnRH release and possibly gene expression in GnRH neurons. This action appears to be mediated through prolactin receptors expressed by the cells.